Assessment of soil parameters during post-liquefaction reconsolidation of loose sand - Zeybek, Abduelhakim; Madabhushi, Gopal Santana Phani (Elsevier Sci Ltd, 2023)
Saturated deposits of loose sand may suffer liquefaction under earthquake shaking. Liquefaction-induced damage occurs during the earthquake loading and may continue during the post-liquefaction reconsolidation stage in which excess pore pressures gradually dissipate. An accurate evaluation of soil parameters is of great significance for the full depiction of this process. Consolidation-related problems are typically investigated using Terzaghi's one-dimensional consolidation theory, assuming a constant permeability, one-dimensional stiffness, and consolidation coefficient throughout this process. Some studies based on physical model tests suggest that an assumption of a single and constant value of soil parameter is not appropriate to study the reconsolidation of liquefied sand. This paper presents the results of three geotechnical centrifuge experiments to contribute to the current understanding of this phenomenon. The centrifuge data is combined with oedometer and fluidization test data, producing several empirical relationships to estimate the soil parameters related to the reconsolidation of liquefied sand. A simplified method is adopted to reproduce the time histories of excess pore pressure dissipation and ground surface settlement using the estimated soil parameters as the input. It is shown that the coefficient of consolidation and one-dimensional stiffness vary as a function of effective stress or excess pore pressure ratio, markedly increasing during the reconsolidation of liquefied sand. The predictions of the proposed methodology appear to match the experimental measurements reasonably well as long as appropriate soil parameters are used.
Keywords: Earthquake; Soil liquefaction; Reconsolidation; Centrifuge modeling; Excess Pore Pressure; Solidification; Permeability; Dissipation